Scopolamine Impairs Spatial Information Recorded With “Miniscope” Calcium Imaging in Hippocampal Place Cells - Sun, Dechuan; Unnithan, Ranjith Rajasekharan; French, Chris (Frontiers in Neuroscience, 2021)
The hippocampus and associated cholinergic inputs have important roles in spatial memory in rodents. Muscarinic blockade with scopolamine results in cognitive deficits usually attributed to impaired memory encoding, but effects on memory retrieval are controversial. We tested the effects of blocking muscarinic acetylcholine receptors (mAChRs) on hippocampal network activity and neural ensembles that had previously encoded spatial information. The activity of hundreds of neurons in mouse hippocampal CA1 was recorded using calcium imaging with a miniaturised fluorescent microscope. The properties of place cells and neuronal ensemble behaviour in a linear track environment were observed. We found decoding accuracy and ensemble stability were significantly reduced after the administration of scopolamine. Several other parameters, including neural firing rate, total number of active neurons, place cell number and spatial information content were affected. Similar results were also observed in a simulated hippocampal network model. This study enhances the understanding of cholinergic blockade on spatial memory impairment.